2016
DOI: 10.1186/s13643-016-0263-z
|View full text |Cite
|
Sign up to set email alerts
|

SWIFT-Review: a text-mining workbench for systematic review

Abstract: BackgroundThere is growing interest in using machine learning approaches to priority rank studies and reduce human burden in screening literature when conducting systematic reviews. In addition, identifying addressable questions during the problem formulation phase of systematic review can be challenging, especially for topics having a large literature base. Here, we assess the performance of the SWIFT-Review priority ranking algorithm for identifying studies relevant to a given research question. We also expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 19 publications
0
148
0
2
Order By: Relevance
“…The system is interoperable with a related desktop application, SWIFT‐Review, which is freely available. A cross‐validation evaluation across 20 previously completed reviews, including 15 from Cohen et al, has shown consistent work saved over sampling.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is interoperable with a related desktop application, SWIFT‐Review, which is freely available. A cross‐validation evaluation across 20 previously completed reviews, including 15 from Cohen et al, has shown consistent work saved over sampling.…”
Section: Related Workmentioning
confidence: 99%
“…References with the same topic or cluster may be thematically related even if there are no common keywords they all share. Furthermore, the topic proportions of each reference can be used to find related references, and as a feature representation for machine learning . Primarily, clusters and topics, supplemented with automatically generated descriptions, allow reviewers to explore the thematic coverage and locate relevant references, without having to explicitly form keyword queries, within diverse collections.…”
Section: Introductionmentioning
confidence: 99%
“…Our review, which required major investment in time and human capital, ultimately only yielded a small number of relevant studies even as initial searches suggested more than 50,000 might be relevant. Machine learning and other technological methods are increasingly available to aid in systematic reviews at the title and abstract and full text stages [63] and other approaches are now available to help use a broader range of datasets (e.g. Google Scholar) [64].…”
Section: Review Limitationsmentioning
confidence: 99%
“…For example, SWIFT-review provides a workbench with tools to assist the reviewer in literature prioritisation (Howard et al, 2016). Using these tools, the reviewer can determine which articles to screen first, thereby reducing the amount of time spent on irrelevant papers.…”
Section: Retrieval and Screening Stage Of A Systematic Reviewmentioning
confidence: 99%